2012
DOI: 10.1051/epjconf/20123812003
|View full text |Cite
|
Sign up to set email alerts
|

Total and partial photoneutron reactions cross sections – new analysis and evaluation

Abstract: Abstract.The well-known problems of significant disagreements between partial photoneutron reactions (,n), (,2n) and (,3n) cross sections data obtained in various experiments are discussed. Using new objective criteria of data reliability it was shown that majority of data under discussion contains significant distortions because of definite shortcomings of experimental photoneutron multiplicity sorting methods used -the majority of experimental data obtained such methods are not reliable. These criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…For 181 Ta,197 Au and 209 Bi it was shown that the newly evaluated partial reaction cross sections agree with the data obtained using the activation method [18,19] and therefore are reliable. It was found that for many nuclei the experimental partial reaction cross sections do not satisfy the proposed data reliability criteria and are noticeably different from evaluated cross sections [6][7][8][9][10][11][12][13][14][15]20]. It was shown that the main reason of that is unreliable transmission of many neutrons from one partial reaction to another because of shortcomings of procedures used to separate counts into 1n and 2n events.…”
Section: The Experimental-theoretical Methods For Reliable Cross-sectimentioning
confidence: 91%
See 3 more Smart Citations
“…For 181 Ta,197 Au and 209 Bi it was shown that the newly evaluated partial reaction cross sections agree with the data obtained using the activation method [18,19] and therefore are reliable. It was found that for many nuclei the experimental partial reaction cross sections do not satisfy the proposed data reliability criteria and are noticeably different from evaluated cross sections [6][7][8][9][10][11][12][13][14][15]20]. It was shown that the main reason of that is unreliable transmission of many neutrons from one partial reaction to another because of shortcomings of procedures used to separate counts into 1n and 2n events.…”
Section: The Experimental-theoretical Methods For Reliable Cross-sectimentioning
confidence: 91%
“…Lines -calculated [16,17] (γ, 1n1p) reaction cross-section. to many other nuclei [6][7][8][9][10][11][12][13][14][15]20] the main reason of significant disagreements between data obtained at Saclay and Livermore for 75 As and 181 Ta is unreliable (erroneous) sorting of photoneutrons from (γ, 1n) and (γ, 2n) reactions [10,15]. In addition in the cases of both nuclei there are the uncertainties because of lost of many neutrons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is obvious that the discrepancy between the Livermore and Saclay data could not be removed by applying a constant normalization factor. It was shown [4][5][6][7][8][9][10][11][12][13][14] that the reasons are the definite shortcomings of neutron multiplicitysorting method based on the idea that energies of neutrons from the partial reactions are noticeably different and neutron multiplicities could be deduced from its measured kinetic energies. The experimental-theoretical method for evaluation the partial reaction cross sections was developed [4] in order to resolve these problems.…”
Section: Introductionmentioning
confidence: 99%